Semi-wrapping lateral cartilage to a square edged strut perpendicularly to prevent collapse in external nasal valve dysfunction: pseudodome technique - Yanılmaz, Muhammed; Akduman, Davut (The European Research Journal, 2019)
Objectives: During inhalation through the nose, the weakness of lateral cartilage may cause the collapse of nasal vestibule and sidewall, causing the complaint of difficult breathing through the nose. We aimed to support the lateral cartilage with a square edged strut to resolve this problem.Methods: We described a technique in 8 cases (5 males, 3 females). In this technique the lateral cartilage is semi wrapped from the underside to a square edged strut, and arched to outside with an open approach rhinoplasty. As it was only a physical support and did not create a new canting up through the skin, we named this maneuver as pseudodome technique. Results: All patients experienced relief of symptoms and no complications observed. The reinforcement effect of the strut was effective in preventing collapse of the nasal alar sidewall as well as did not cause contour irregularities. Conclusions: Pseudodome technique can be performed for acquired or congenital nasal sidewall collapse caused by lower lateral cartilage structural weaknesses successfully.